Comparison of thiazides and amiloride in treatment of moderate hypertension. Issue 6383 (25th June 1983) - Thomas, J P; Thomson, W H
Abstract : The biochemical disturbance produced by thiazide diuretics and by amiloride during treatment of moderate hypertension were compared. Two parallel studies were initiated. In one 40 patients with newly diagnosed hypertension were treated with metoprolol and a diuretic, either hydrochlorothiazide or amiloride. In a second study 38 patients receiving longstanding treatment with hypotensives and thiazides either continued the treatment or replaced the thiazide with amiloride. Initial biochemical assessments were compared with those after two years in the study. In previously untreated patients, thiazide produced a significant fall in plasma potassium and hyperuricaemia that did not occur with amiloride (p less than 0.001). Those patients receiving long term treatment for their hypertension who continued to take thiazides had persistent hypokalaemia and hyperuricaemia. Substitution with amiloride corrected the hypokalaemia and serum uric acid returned toward normal ranges, but this change was not statistically significant. Patients receiving long term treatment also had impaired glucose tolerance, this remained unchanged in those receiving thiazide but was corrected in those receiving amiloride. Compared with amiloride thiazides produced undesirable but reversible biochemical changes. As control of hypertension was equally effective with both preparations, we suggest that a combination of amiloride with a beta blocker in treatment of moderate hypertension in preferred.